1999
DOI: 10.1148/radiology.210.1.r99ja0725
|View full text |Cite
|
Sign up to set email alerts
|

Filling In of Radiation Therapy-induced Bronchiectatic Change: A Reliable Sign of Locally Recurrent Lung Cancer

Abstract: Filling in of radiation therapy-induced bronchiectatic change is a reliable CT sign of locally recurrent lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Matsuo et al [40] reported that, among other factors, only growth of consolidation after 12 months on CT was a statistically relevant predictor of recurrence. Otherwise, other findings already described as signs of recurrence after conventional radiotherapy can be used to suspect recurrence after SBRT; these include the filling of radiation-induced ectatic bronchi [41], development of bulging at margins of radiation-induced consolidation, and [39]. PET-CT is also a helpful technique for early detection of recurrence after SBRT, even though it needs to be applied in conjunction with other techniques [42].…”
Section: Parenchymal and Bronchial Recurrencementioning
confidence: 99%
“…Matsuo et al [40] reported that, among other factors, only growth of consolidation after 12 months on CT was a statistically relevant predictor of recurrence. Otherwise, other findings already described as signs of recurrence after conventional radiotherapy can be used to suspect recurrence after SBRT; these include the filling of radiation-induced ectatic bronchi [41], development of bulging at margins of radiation-induced consolidation, and [39]. PET-CT is also a helpful technique for early detection of recurrence after SBRT, even though it needs to be applied in conjunction with other techniques [42].…”
Section: Parenchymal and Bronchial Recurrencementioning
confidence: 99%
“…Moreover, chest CT can detect changes consistent with cancer recurrence earlier than can chest radiography [14]. Additionally, Chiu et al [15] have reported that low-dose CT Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It was the first sign of recurrence in six patients. Eight patients with stable radiation-induced fibrosis and patent bronchi remained disease-free [51].…”
Section: Control After Treatment/tumour Recurrencementioning
confidence: 99%